2018
DOI: 10.1177/2042753018811871
|View full text |Cite
|
Sign up to set email alerts
|

Critical hybrid pedagogies: A self-study inquiry into faculty practices in a blended Educational Leadership EdD program

Abstract: In an educational context that includes an overarching neoliberal agenda and rapidly expanding inequalities that cross social, racial, class, linguistic, and gender lines, preparing educational leaders to promote social justice in educational systems is more urgent than ever. Framed by critical posthumanism, this self-study inquiry investigates the construction of hybrid teaching practices that foster the kind of authentic interaction needed to develop transformative leaders who are capable of challenging unju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Evans et al (2020) reported that teachers successfully engaged with blended learning to support their student and made extensive use of features and tools of the adopted LMS after their participation in a professional development training course. Previous studies (Antwi-Boampong, 2020; Strom and Porfilio, 2019) have also highlighted the necessity of professional development training for the teachers for better understanding of the blended learning pedagogy and improved teaching practices for overall motivation and willingness of the teachers. Overall, it can be said that teachers have to play a significant role in successfully attaining the goal of blended learning.…”
Section: Introductionmentioning
confidence: 99%
“…Evans et al (2020) reported that teachers successfully engaged with blended learning to support their student and made extensive use of features and tools of the adopted LMS after their participation in a professional development training course. Previous studies (Antwi-Boampong, 2020; Strom and Porfilio, 2019) have also highlighted the necessity of professional development training for the teachers for better understanding of the blended learning pedagogy and improved teaching practices for overall motivation and willingness of the teachers. Overall, it can be said that teachers have to play a significant role in successfully attaining the goal of blended learning.…”
Section: Introductionmentioning
confidence: 99%
“…Improvers stood out in their written reflections as well is in the initiative they took in various instances during class. Following a whole-class discussion over the articles by West (2019) and Strom and Porfilio (2019), small groups came up with learning objectives on ELA topics of their choice that synthesized the articles’ notions of critical pedagogy and technology-mediated operations. After groups shared their objectives aloud with the larger class, volunteers from each group wrote their objectives out on the white board.…”
Section: Resultsmentioning
confidence: 99%
“…As we hope to steer preservice teachers toward ontological considerations, we find this chapter to be instructive. More recent NLS scholarship helps preservice teachers situate themselves as practitioners within the digital age, simultaneously developing effective approaches to navigate technology-mediated classrooms (West, 2019) along with critical hybrid pedagogies (Strom and Porfilio, 2019) that utilize a critical lens to account for social justice issues. Students initiate themselves by exploring how literacy education, through and alongside digital texts, is more interactive and interdisciplinary than ever before.…”
Section: Methodsmentioning
confidence: 99%
“…This study reviewed a substantial number of DiPs, but selfreport data from students, such as end-of program survey responses and student interviews were not included in the analysis. Future research should include additional types of data that can provide a more comprehensive understanding of students' experiences designing a DiP (e.g., Amrein-Beardsley et al, 2012;Strom & Porfilio, 2019). The findings presented here represent one program's dissertation studies, so the results should not be generalized to other contexts, degrees, and programs.…”
Section: Study Limitations and Future Researchmentioning
confidence: 99%